2017
DOI: 10.3390/s17102296
|View full text |Cite
|
Sign up to set email alerts
|

An IoT-Based Solution for Monitoring a Fleet of Educational Buildings Focusing on Energy Efficiency

Abstract: Raising awareness among young people and changing their behaviour and habits concerning energy usage is key to achieving sustained energy saving. Additionally, young people are very sensitive to environmental protection so raising awareness among children is much easier than with any other group of citizens. This work examines ways to create an innovative Information & Communication Technologies (ICT) ecosystem (including web-based, mobile, social and sensing elements) tailored specifically for school environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…Our approach aims to provide a monitoring framework that allow the continuous evaluation of the conditions of classrooms. The GAIA platform [6] provides real-time monitoring of 18 school buildings (see Table 1), spread in 3 countries (Greece, Italy, Sweden), covering a range of local climatic conditions and educational levels (primary, secondary and high school). In each of the 18 buildings participating in the GAIA platform, sensor devices are deployed that measure (a) the overall power consumption of the building, (b) the environmental comfort within each individual classroom and (c) the weather conditions and air pollution levels in each building.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach aims to provide a monitoring framework that allow the continuous evaluation of the conditions of classrooms. The GAIA platform [6] provides real-time monitoring of 18 school buildings (see Table 1), spread in 3 countries (Greece, Italy, Sweden), covering a range of local climatic conditions and educational levels (primary, secondary and high school). In each of the 18 buildings participating in the GAIA platform, sensor devices are deployed that measure (a) the overall power consumption of the building, (b) the environmental comfort within each individual classroom and (c) the weather conditions and air pollution levels in each building.…”
Section: Related Workmentioning
confidence: 99%
“…1. For a detailed introduction to the platform, the provided services and the implemented applications see [6,9,11,13,14]. The IoT devices can be split into 3 different categories based on their origin and operation type: Power Consumption These devices are situated on the general electricity distribution board of each building to measure the power consumption of each one of the 3-phase power supply.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, nonelectrical parameters could be measured using special transducers to sense heating, ventilation, and air conditioning (HVAC) parameters like temperature, humidity, carbon dioxide, and airflow . Moreover, recent works have proposed smart school building structure to reinforce the education sector on promoting efficient energy usage …”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, recent works have proposed smart school building structure to reinforce the education sector on promoting efficient energy usage. [18][19][20] Smart meters are used to manage energy consumption by controlling the switching of different electric equipment over different times of the day based on energy analysis and loads' profiles. 21 Furthermore, Internet of Things (IoT) has a prime rule in making the monitoring systems in smart buildings into an efficient energy management systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, during our ethnographic studies and online surveys with the occupants of the pilot sites of ChArGED, we found that observing actions of others would violate their privacy concerns and that penalizing users for their non-energy efficient behavior would completely demotivate them to engage into the game in the first place. In the context of other public buildings, Amaxilatis et al [13] aim to increase energy awareness and alter energy-consumption behaviors of children through educational activities in schools. Johnson et al [14] reviewed multiple energy-saving competitions among university students and identified several pitfalls in their design.…”
Section: Introductionmentioning
confidence: 99%